Soil physical fertility viz-a-viz climate resilient agriculture - Bhatt, Rajan (2025)
Sustainable agriculture faces numerous challenges, including diminishing soil and water resources, declining soil health, and escalating input costs. This review focuses on advancements in soil physics and their implications for enhancing crop productivity and resource use efficiency. It highlights the critical relationships between soil physical properties and agricultural practices, emphasizing the flow of water, gases, and nutrients within the soil system. Key developments in understanding water infiltration, moisture retention, heat transfer, and gas exchange are discussed, along with their impact on plant growth and yield. Various modeling approaches are explored to address complex soil-water-nutrient interactions, aiming to improve agricultural outcomes. The review identifies significant knowledge gaps, particularly concerning soil microstructure and the integration of soil-plant-atmosphere dynamics. Future research should prioritize the application of innovative technologies, such as remote sensing, machine learning, and advanced imaging techniques, to enhance our understanding of soil processes. By focusing on these areas, sustainable soil management practices can be developed, ensuring optimal resource use while safeguarding environmental health. This review underscores the necessity of a multidisciplinary approach to soil physics, aiming to foster sustainable agricultural practices that can adapt to the challenges of modern farming.